ACCESSIBILITY OF SPORT BUILDINGS FOR PEOPLE WITH DISABILITIES - INTERVENTION OF REHABILITATION NURSES - Cindy Simões da Silva; Maria Manuela Ferreira Pereira da Silva Martins; Rute Salomé Silva Pereira; Maria Neto Pacheco; Ana Eduarda Carvalho; Wiliam César Alves Machado (Associação Portuguesa dos Enfermeiros de Reabilitação, 2019)
Background: The nurse specialist in rehabilitation nursing is essential in the involvement of people with disabilities in sports practices. Its role is to intervene in deviations of health of the person and to evaluate the accessibility of the building. Objectives: Analyze architectural barriers in the building and analyze the differences taking into account the typology of the building and their location. Methodology: Quantitative paradigm of descriptive and transversal nature. A universe composed of 9 public sports buildings of a Municipality. The data collection instrument is an observation grid built from the legislation in force. The treatment of data using simple descriptive statistics and chi-square. Results: There are architectural barriers in buildings, but there have been no significant differences in accessibility conditions between pool and field buildings or between buildings located in the city or periphery Conclusion: In the municipality under study, people with disabilities have difficulty accessing suitable places to practice some sports activities. Rehabilitation nurses should evaluate the enclosures in relation to architectural barriers to make proper counseling and sensitization to the local authority in order to make it more inclusive.